FACTORS AFFECTING MUDHARABAH FINANCING IN ISLAMIC BANKS IN INDONESIA - Muhamad Agung Japalsyah; Mohamad Zulman Hakim (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
Abstract            The purpose of this study is to determine the factors that influence mudharabah financing in Islamic commercial banks in Indonesia. The research time period used is 4 years, namely the 2016-2019 period.The population of this study includes Islamic commercial banks registered with the Otoritas Jasa Keuangan (OJK) for the period 2016-2019. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 10 Islamic commercial banks were obtained. The type of data used is secondary data obtained from the sites of each Islamic commercial bank. The analysis method used is panel data regression analysis.From this research, it shows that Third Party Funds (TPF) have a positive effect on Mudharabah Financing, Capital Adequacy Ratio (CAR) has no effect on Mudharabah Financing, Net Performing Financing (NPF) has no effect on Mudharabah Financing and the Financing to Deposit Ratio (FDR) has no effect. against Mudharabah financing.